1999
DOI: 10.1021/jp983150t
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Acetylperoxy + HO2 Reaction

Abstract: The reaction of HO 2 with CH 3 C(O)O 2 is examined using flash photolysis and FTIR smog chamber techniques. Time-resolved UV spectroscopy is used to follow the transient peroxy species. It yields reasonable concentration versus time profiles for CH 3 C(O)O 2 and HO 2 , but indicates anomalously high levels of secondary CH 3 O 2 radicals. Transient IR diode laser absorption confirms the HO 2 decay rates; however, the anticipated reaction model substantially underestimates the observed decay. The model is augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
113
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(136 citation statements)
references
References 31 publications
18
113
5
Order By: Relevance
“…This work fitted k (R5) 0.38 ± 0.08 0.12 ± 0.02 0.50 ± 0.08 3.1 ± 0.3 2.1 b 0.37 ± 0.10 0.12 ± 0.04 0.51 ± 0.12 3.2 ± 0.2 2.4 ± 0.4 Groß et al (2014b) 0.23 ± 0.12 0.16 ± 0.08 0.61 ± 0.09 1.44 2.1 ± 0.4 Dillon and Crowley (2008) --0.50 ± 0.20 -1.4 ± 0.5 Jenkin et al (2007) 0.38 ± 0.13 0.12 ± 0.04 0.43 ± 0.10 3.16 ± 0.48 (1.4 c ) Le Crâne et al (2006) -0.20 ± 0.01 < 0.1 -1.50 ± 0.08 Hasson et al (2004) 0.40 ± 0.16 0.20 ± 0.08 0.40 ± 0.16 2.00 ± 0.57 2.2 Tomas et al (2001) -0.20 ± 0.02 --1.51 ± 0.07 Crawford et al (1999) (0.72) c 0.12 ± 0.04 -7.3 (2.6) d 4.4 ± 1.6 Horie and Moortgat (1992) ---2.7 - Moortgat et al (1989) -0.33 ± 0.07 --1.3 ± 0.3 Niki et al (1985) ∼ 0.75 ∼ 0.25 -∼ 3 -IUPAC (Atkinson et al, 2006) Crawford et al (1999) corrected for erroneous absorption cross section for CH 3 C(O)OOH by Orlando et al (2000).…”
Section: Secondary Oh Productionmentioning
confidence: 96%
See 3 more Smart Citations
“…This work fitted k (R5) 0.38 ± 0.08 0.12 ± 0.02 0.50 ± 0.08 3.1 ± 0.3 2.1 b 0.37 ± 0.10 0.12 ± 0.04 0.51 ± 0.12 3.2 ± 0.2 2.4 ± 0.4 Groß et al (2014b) 0.23 ± 0.12 0.16 ± 0.08 0.61 ± 0.09 1.44 2.1 ± 0.4 Dillon and Crowley (2008) --0.50 ± 0.20 -1.4 ± 0.5 Jenkin et al (2007) 0.38 ± 0.13 0.12 ± 0.04 0.43 ± 0.10 3.16 ± 0.48 (1.4 c ) Le Crâne et al (2006) -0.20 ± 0.01 < 0.1 -1.50 ± 0.08 Hasson et al (2004) 0.40 ± 0.16 0.20 ± 0.08 0.40 ± 0.16 2.00 ± 0.57 2.2 Tomas et al (2001) -0.20 ± 0.02 --1.51 ± 0.07 Crawford et al (1999) (0.72) c 0.12 ± 0.04 -7.3 (2.6) d 4.4 ± 1.6 Horie and Moortgat (1992) ---2.7 - Moortgat et al (1989) -0.33 ± 0.07 --1.3 ± 0.3 Niki et al (1985) ∼ 0.75 ∼ 0.25 -∼ 3 -IUPAC (Atkinson et al, 2006) Crawford et al (1999) corrected for erroneous absorption cross section for CH 3 C(O)OOH by Orlando et al (2000).…”
Section: Secondary Oh Productionmentioning
confidence: 96%
“…k (R5a) /k (R5b) has been estimated as 3.2 ± 0.2 across the all experiments presented here, which is in agreement with the IUPAC recommendation and others all the way back to the first investigation of the reaction by Niki et al (1985), which was insensitive to Reaction (R5c). The high measurement of k (R5a) by Crawford et al (1999) was corrected for the CH 3 C(O)OOH absorption cross-section by Orlando et al (2000), calculating k (R5a) /k (R5b) = 2.6, in line with other reported values. The preservation of this ratio in the work presented here helps substantiate a higher rate coefficient for Reaction (R5c), although this does not correlate with the more recent study by Groß et al (2014b), where k (R5a) /k (R5b) = 1.44.…”
Section: Determination Of K (R5)mentioning
confidence: 96%
See 2 more Smart Citations
“…Recent experimental and theoretical work has, however, suggested that the reactions of HO 2 with some substituted RO 2 , do not exclusively terminate radical chemistry (Thornton et al, 2002). For the reaction (R1) of HO 2 with acetyl peroxyl, CH 3 C(O)O 2 , Hasson and coworkers reported a significant yield of OH radicals (R1c) (Hasson et al, 2004), in addition to the well-established radical terminating peracid (R1a) and O 3 (R1b) products (Niki et al, 1985;Moortgat et al, 1989;Horie and Moortgat, 1992;Crawford et al, 1999;Tomas et al, 2001). …”
Section: Introductionmentioning
confidence: 99%